Combining radiographic, urodynamic and ultrasonographic techniques for the evaluation of urinary bladder structure and function in an animal model - Salah AS; Angela Ng MH; Christopher Ho CK; Ismail S; Ruszymah BHI; Zulkifili MDZ (Department of Surgery, UKM Medical Centre, 2011)
The urinary bladder can be affected by either congenital or acquired disease leading to small, noncompliant, hypertonic urinary bladder with subsequent transfer of high pressure to upper tract leading to renal function deterioration and renal failure. The aim of urinary bladder reconstruction was to restore normal structure and functions of the urinary bladder. Successful reconstructions should be confirmed by measurement and evaluation of bladder structure and functions. In this study, different modalities such as radiography (CT scan), ultrasonography, and urodynamic were used to assess urinary bladder structure and functions in an animal model. The radiographic (CT scan) and ultrasonography have mostly structural data, while urodynamic studies produce functional parameters. Using these combined modalities we could measure and determine the normal urinary bladder volume, bladder filling pressure, voiding pressure, bladder shape, outline border, three dimension (3D) configurations, locations, and bladder dimensions. Radiography showed bladder as oval, contrast filled hollow organ, localized centrally. Mean bladder volume was 1.42 ml±0.03. Ultrasonography showed bladder as oval, elongated hypo echoic urine filled organ with, wall thickness 1mm at bladder dome and 2mm at bladder base. Mean volume was 1.44 ml±0.05. Urodynamic study showed low intravesical filling pressure with a mean value of 6-5 cm H2O, while the mean voiding pressure was 18-19cmH2O. Mean bladder volume was 1.40 ml±0.02. The acquired data for the normal (control) animals may be used as a reference for further evaluations of our future research on urinary bladder reconstructions using tissue engineering technology.